2019
DOI: 10.1177/0192623319878402
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Variations in Air Pollution Health Effects: Incorporating Neuroendocrine Activation

Abstract: Diverse host factors/phenotypes may exacerbate or diminish biological responses induced by air pollutant exposure. We lack an understanding of biological indicators of environmental exposures that culminate in a physiological response versus those that lead to adversity. Variations in response phenotype might arise centrally and/or at the local tissue level. In addition to genetic differences, the current evidence supports the roles of preexisting cardiopulmonary diseases, diabetes, diet, adverse prenatal envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 155 publications
(209 reference statements)
0
9
0
Order By: Relevance
“…Ozone has been extensively studied for its pulmonary effects; however, more recently neurological and systemic effects have also been reported 8 . We have shown that similar to many non-chemical (psychosocial) stressors 9 , a single acute ozone inhalation produces a myriad of changes in metabolic and immunological processes through sympathetic and hypothalamic neuroendocrine stress pathway activation 10,11 . Thus, acute ozone exposure as a stressor may alter a broad spectrum of homeostatic processes, which in susceptible individuals may contribute to exacerbation of metabolic disease.…”
Section: Ghmentioning
confidence: 99%
“…Ozone has been extensively studied for its pulmonary effects; however, more recently neurological and systemic effects have also been reported 8 . We have shown that similar to many non-chemical (psychosocial) stressors 9 , a single acute ozone inhalation produces a myriad of changes in metabolic and immunological processes through sympathetic and hypothalamic neuroendocrine stress pathway activation 10,11 . Thus, acute ozone exposure as a stressor may alter a broad spectrum of homeostatic processes, which in susceptible individuals may contribute to exacerbation of metabolic disease.…”
Section: Ghmentioning
confidence: 99%
“…In addition, repeated episodic exposures may result in an attenuation of the ozone-induced effects, possibly due to the initiation of an adaptive response. Some evidence indicates that neurohumoral sympathetic modulation may be involved in the mechanism of ozoneinduced fasting hyperglycemia and glucose intolerance (Bass et al 2013;Kodavanti et al 2015;Kodavanti 2019). In particular, the hypothesis suggests that ozone induces a neuroendocrine stress response, activating the hypothalamic-pituitaryadrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes, which can lead to increased circulating epinephrine and glucocorticoids, including corticosterone, although the available data are not consistent (Miller et al 2015;Snow et al 2018;Henriquez et al 2019Henriquez et al , 2020.…”
Section: Relationship Of the Results Of This Review To Mechanistic Informationmentioning
confidence: 99%
“…In addition, exacerbation of ozone-induced systemic effects has been reported in rats treated with b 2 -adrenergic and glucocorticoid receptor agonists, whereas these effects are mitigated in rats treated with adrenergic and glucocorticoid receptor antagonists (Snow et al 2018;Henriquez et al 2019Henriquez et al , 2020. Emerging evidence suggests that the tissue distribution of these receptors, along with the presence of individual variability, may represent a critical factor in these specific ozone-induced metabolic effects (Kodavanti 2019). Although some data report that ozone has been shown to activate the HPA and SAM axes, the initiating events of autonomic activation remain unclear, particularly the role of vagal sensory nerves and/or circulating mediators that may act on different brain regions, such as the hypothalamus.…”
Section: Relationship Of the Results Of This Review To Mechanistic Informationmentioning
confidence: 99%
“…Although local pulmonary cellular changes have been characterized extensively with acute exposure to different pollutants, the mechanisms by which the immune response is activated and immune cells are recruited from lymphoid organs, matured, and extravasated to the site of injury are not well understood. Our recent studies have shown that the adrenergic and glucocorticoid pathways are involved in pulmonary vascular leakage and inflammatory response induced by irritant pollutants, such as ozone [14,81,82]. In light of recent research into the marked effects of air pollutants on the brain [7,[82][83][84], and the involvement of the neuroendocrine system with increased adrenal-derived stress hormones [85], it is conceivable that AR and GR activation are involved in the health effects of air pollution.…”
Section: Ars and Grs In Air-pollutant-induced Lung Injury And Inflammationmentioning
confidence: 99%
“…Our recent studies have shown that the adrenergic and glucocorticoid pathways are involved in pulmonary vascular leakage and inflammatory response induced by irritant pollutants, such as ozone [14,81,82]. In light of recent research into the marked effects of air pollutants on the brain [7,[82][83][84], and the involvement of the neuroendocrine system with increased adrenal-derived stress hormones [85], it is conceivable that AR and GR activation are involved in the health effects of air pollution. Understanding the roles of these receptors may explain how a pulmonary inflammatory response is generated after exposure to air pollutants, why there is tolerance or adaptation to this initial pulmonary response, how individuals with psychosocial disorders and altered neuroendocrine regulation may be more susceptible, and what systemic mediators are critical for initial injury and inflammation.…”
Section: Ars and Grs In Air-pollutant-induced Lung Injury And Inflammationmentioning
confidence: 99%